2023
DOI: 10.1088/1741-4326/ad0acd
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of edge temperature ring oscillation during the stationary improved confinement mode in EAST

A.D. Liu,
X.L. Zou,
X.M. Zhong
et al.

Abstract: The I-mode is a natural edge localized mode (ELM)-free regime with H-mode-like improved energy confinement and L-mode-like particle confinement, making it an attractive scenario for future tokamak-based fusion reactors. A kind of low-frequency oscillation has been widely observed, with a frequency between stationary zonal flow and geodesic-acoustic mode (GAM) zonal flow. In EAST, most stationary I-mode shots have such a mode, called edge temperature ring oscillation (ETRO). This mode probably plays an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…However, this phenomenon is different in EAST. Similar to the phenomenon observed in C-Mod and AUG, a low-frequency toroidal symmetric mode, edge temperature oscillation (ETRO) [16], is present in the I-mode on EAST and has been observed in 90% of the discharges [17]. However, it has been confirmed that ETRO is not GAM [17].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, this phenomenon is different in EAST. Similar to the phenomenon observed in C-Mod and AUG, a low-frequency toroidal symmetric mode, edge temperature oscillation (ETRO) [16], is present in the I-mode on EAST and has been observed in 90% of the discharges [17]. However, it has been confirmed that ETRO is not GAM [17].…”
Section: Introductionsupporting
confidence: 64%
“…A mode with a characteristic frequency of approximately 5 Hz is evident in the timefrequency spectrum of the envelope, indicating its modulation of high-frequency density fluctuations. Simultaneously, this mode is observed in other signals, including ECE in the edge (ρ ∼ 0.9), divertor LP, DR, SXR, AXUV, and Mirnov coils [17]. Based on these features, it is identified as the ETRO.…”
Section: Wcm Visible In Pcrmentioning
confidence: 77%